PERAN EMPATI GURU DAN KETERBUKAAN DIRI (SELF-DISCLOSURE) DALAM MEMBANGUN RELASI PEDAGOGIS YANG INKLUSIF DI MTS MUKHTAR SYAFA’AT BLOKAGUNG - Muhammad Ridwan; Ro'fat Hizmatul Himmah (Ma Chung Press, 2026)
This study aims to explore the role of teacher empathy and self-disclosure in building inclusive pedagogical relationships at MTs Mukhtar Syafa’at Blokagung. The primary challenge in modern education, particularly within the pesantren (Islamic boarding school) environment, is the emotional distance and rigid hierarchical structures that hinder the process of knowledge transfer and character building. This research employs a qualitative approach with a phenomenological case study design. Data were collected through participant observation, in-depth interviews with teachers and students, and documentation studies. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing according to the Miles and Huberman model. The results indicate that teacher empathy serves as the core foundation in creating an inclusive classroom climate, where teachers act as active listeners who validate the diverse backgrounds of the students (santri). Measured and proportional self-disclosure practices proved to be a catalyst in building trust and dismantling rigid formalities without diminishing the teacher's authority (marwah). The synergy between empathy and self-disclosure creates a